(untitled) (International Journal of Physiotherapy, 2016)
Background: Low back pain is the most undesirable phase of women. Every pregnant woman would suffer from low back pain with mild or severe intensity. Various methods and forms of treatment have been practised to relive low back pain during child bearing phase without causing any harm to the developing foetus. This study has focussed on yoga to relieve the pain and disabilities due to low back pain in primi gravida women. Objective: To evaluate the effectiveness of yoga postures in reducing the low back pain and disability due to low back pain in second trimester of prima gravidas. Methods: Primi gravida women with low back pain were randomised to 2 groups, group-1 and group-2. The study was conducted for 8weeks and included 70 patients with 35 in group-1 and 30 in group-2. There were 5 drop outs. The selection criteria were based on patients suffering from low back pain which was further restricting their normal daily activities. The pain was assessed with VAS score of 0-10 with mean of 5.6 and 6.2 respectively in experimental and control group respectively before the treatment and disabilities were assessed with MODI with mean score 52% and 57 % respectively before treatment. The Group-1 was treated with yoga postures and group-2 by gynaecologists’ advice with acetaminophen, external topical gel and moist heat modalities. Results: The study concluded that there was significant reduction of pain on VAS score (p<0.001) and reduced disabilities on MODI (p<0.001) in both the groups. The statistical analysis showed there was significance within the interventional group and also within control group. Whereas the analysis done between the groups showed high significance of the interventional group having better recovery than the control group at the end of 8 weeks. Conclusion: Yoga postures had higher benefits in alleviating the low back pain and reducing disabilities related to low back pain in primi gravidas.